Development of Simulation Model of Power Installations for power Supply for Agricultural Consumers (Eurasian Research Bulletin, 2022)
This problem is urgent, since, according to the forecasts of most scientists, the reserves of natural resources used in the electric power industry have been rapidly declining lately, due to the growth of human energy needs. The development of energy is a very important task that can solve the problem of lack of fuel to meet the needs.